Artistic : Paintings in Mary Poppins Film (1964) (Universitas Pendidikan Indonesia, 2024)
This study discusses the paintings in the film Mary Poppins (1964) which were made manually, aiming for the background set and also supporting the storyline in the form of paintings. Setting of place is an important thing in the process of film making. Sometimes filmmakers use matte painting to create the illusion of an environment that doesn't exist on the set. The storyline of Mary Poppins who enters the world of chalk also uses matte painting to show the change between the world of chalk and the real world. It certainly does not escape the technique of painting. To create realistic settings that are logical and interactive with the actors. The methodology used in this study is a research base design, with steps of concept idea, identification, analysis, implementation and evaluation. This study succeeded in explaining art and design studies on film background from the film Mary Poppins (1964) with the matte painting. This research can be a reference for producer designer who take the matte painting technique and also for general painters. The study from this research can be a reference material for painters, animators, and film makers. The data taken in this study is a study of art and design in paintings with a theme on the storyline. A blend of the art of painting and design for setting the stage for films.